Методические указания по физике для учащихся заочных курсов по подготовке в институт - Коваленок Г. В.; Пудкова З. Н.; Коваленок Э. Д.; Поздняков В. В.; Соколов В. А. Владимир Алексеевич (Томск, 1963)
Ротапринт. изд.